Klasifikasi Penentuan Siswa Berprestasi Menggunakan Algoritma Naïve Bayes Classifier DI PT.Yes Study Education Group Indonesia - Laksono, Novan Ponco; Syaaifullah, Achmad Akbar; Yusuf, Ajif Yunizar Pratama (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2025)
PT. Yes Study Education Group Indonesia is an overseas education consultancy founded by international alumni and based in Toronto, Canada, with experience helping thousands of students from various parts of the world to achieve their dream of studying abroad. However, it is not easy to study abroad because there are several factors and documents that must be prepared, such as passports, visas, and English test certificates like the Test Of English as a Foreign Language (TOEFL) and the International English Language Testing System (IELTS). To achieve optimal results, good learning outcomes are required; furthermore, of course, learning outcomes are indicators of student achievement, so an algorithm is needed to determine student performance, with the aim of serving as a supporting tool in evaluating the learning process and outcomes using the naïve bayes classifier algorithm with a trial dataset of 200 student names along with their respective scores, from which 80 test records were obtained. From these calculations, the Gaussian NB model with a 50:50 split validation yielded an accuracy of 73%, scenario 2 with a 60:40 ratio yielded 75% accuracy, scenario 3 with a 70:30 ratio yielded 76.6% accuracy, scenario 4 with an 80:20 ratio yielded 82.2% accuracy, and scenario 5 with a 90:10 ratio yielded 85% accuracy.